MODULE TECHNOLOGY AS ONE OF FORMS OF EDUCATIONAL PROCESS ORGANIZATION IN OREL STATE AGRARIAN UNIVERSITY NAMED AFTER N.V. PARAKHIN - E. V. Aleksandrova (Erudio Journal of Educational Innovation, 2018)
The article illustrates the necessity to implement the module educational technology into the educational process of The Agrarian University and the reasonability to apply the module approach during the organization of the teaching process of bachelors and masters.